Evaluation Of Mechanism Of Anti-Diabetic Activity Of Terminalia Chebula On Alloxan And Adrenaline Induced Diabetic Albino Rats - RAKTIM BORGOHAIN,; KINGSHUK LAHON,; SWARNAMONI DAS,; KALPANA GOHAIN, (International Journal of Pharma and Bio Sciences, 2012)
Diabetes is one of the major causes of premature disease and death worldwide, with wide prevalence in low and middle income countries like India. Deficiencies in diagnosis and treatment, especially cost factors contribute to the extent of the problem in developing countries. Herbal products are widely available and cost effective, hence we wanted to evaluate the antidiabetic action of ethanolic pulp extract of a locally available plant, Terminalia chebula (AETC) on alloxan induced diabetic rats in comparison to Glibenclamide along with the mechanism of such action. Five groups of albino rats, with six rats in each group were taken for the study. Diabetes was induced in group C, D and E by injecting alloxan 150mg/kg body weight intra-peritoneally. Group A and B received normal saline (5ml/kg/day orally) and AETC (100mg/kg/day orally) respectively for 4 weeks. Groups C, D and E received Normal saline (5ml/kg/day orally), AETC (100mg/kg/day orally) and Glibenclamide (5mg/kg/day orally) respectively for 4 weeks. Fasting blood glucose levels were estimated at the end of 1st, 2nd, 3rd and 4th week. For mechanism of action, glycogen content of liver, heart and skeletal muscle were estimated in alloxan induced rats and action of AETC on blood glucose in adrenaline-induced hyperglycemic rats was evaluated, using normal control, diabetic test (AETC) and diabetic standard (Glibenclamide) groups. Statistical analysis was done using one way ANOVA followed by Dunnet’s multiple comparison test. Diabetic test and standard groups were compared by Unpaired ‘t’ test. A P value of < 0.01 was considered significant. Terminalia chebula showed significant anti-hyperglycemic effect (P<0.01) without hypoglycemic action in normal rats, and efficacy was lower than glibenclamide in alloxan model but higher in adrenaline induced model. The glycogen content of liver significantly increased in diabetes induced albino rat which may be due to insulin like action of ingredients present in Terminalia chebula. T. chebula also showed reduction in blood glucose level on adrenaline induced hyperglycemia resulting from inhibition of α2 receptor of pancreatic β-cells, thus promoting further insulin release.The ethanolic pulp extract of Terminalia chebula fruit has significant anti-diabetic activity probably due to insulin like action of its constituents and promotion of insulin release.